O começo da vida: contribuições da linguagem fílmica para gestantes em relação à primeira infância - Mendes, Paula Rivele Gomes Sousa (2018)
Filmic language works as a movement to start discussions, promoting knowledge and revealing practices and social meanings. It is an interdisciplinar practice that interacts with many contents and understands mechanisms and interfaces through several languages. As the child development happens by interaction and construction of an affective bond since its very conception, one can say that the beginning of life is a priority for civil society, demanding public policies capable of providing a development without adversities. Documentary titled o começo da vida (the beginning of life) approaches this discussion of how people should handle the early childhood stage. Thus, the goal of this work is to analyze the contribuitions of documentary o começo da vida to pregnant women about the early childhood. This work used a qualitative approach, carried out from April to July of 2018, in the town of Alcântaras-CE. 13 pregnant women participated, 9 of them belonging to the Gerando uma nova vida (generating a new life) group, part of CRAS, and 4 belonging to the pregnant women group of UBS Doutor Shigueo Nakamura. To collect data, the projective technique was applied, where the documentary o começo da vida was exhibited dubbed in portuguese. Three sessions were made, two of them in the CRAS and one in the forementioned UBS. After each showing, a dialogue circle was carried out. A schedule of home visits to apply individual interview was constructed, using a semi-structured script. Only two pregnant women chose to do the interview in the UBS. Data was recorded, transcribed and assorted. The empyrical material was processed under discourse analysis. Research was approved by Comitê de Ética em Pesquisa da UFC (UFC Research Ethics Comitee), complying with all of the ethic principles from the Resolução 466/2012 (Resolution 466/2012), of the Conselho Nacional de Saúde do Ministério da Saúde (Ministry of Health National Health Board). Results showed that documentary o começo da vida brought contributions to the pregnant women about care in the early childhood, making them realize new things, motivating them to take positive actions in the care of their children and the still unborn. It has also provided a critical reflection about the importance of participation of the father in the process, about letting the child play freely with nature and objects, about the role of both family and community as a support network. These pregnant women walked between remembering their own childhood and projecting future care with their children. Thus, it is relevant to use this documentary with groups of pregnant women, expanding this to fathers and the family support network, as the moving image educates using feelings and information.